Pembelajaran jarak jauh dengan pendekatan flipped learning dan kepuasannya bagi mahasiswa S1 pendidikan matematika (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
This study aims to determine the efforts made by educator in implementing distance learning so that students understand the material presented and students satisfaction with the efforts of educator in implementing distance learning. This type of research is descriptive qualitative research with subjects totaling 48 people, which are 2 lecturers and 46 undergraduate students. The results obtained in this research are that there are several things that educators are trying to do in implementing distance learning, namely preparing learning carefully from choosing teaching materials, learning media, and appropriate learning methods. From the results of the students questionnaire, it shows that the efforts made by educator in implementing distance learning are able to meet the expectations of students in participating in distance learning, so that students satisfaction arises, where teh dimensions of satisfaction are as expected, and overall satisfaction. From the results of questionnaire, the three dimensions of satisfaction are met, it can be said that students are satisfied with the efforts of educators in implementing distance learning.
Keywords: pandemic covid-19; distance learning; satisfaction